Fractal art and multi-blended spaces. Issue 1 (1st December 2019) - Kowsari, Masoud; Garousi, Mehrdad
AbstractArtworks, especially in the last two centuries, have been more created through a process of blending than at any other time. This blendedness is seen not only in many modern and postmodern works of art, from German expressionist woodcuts to Picasso's paintings and spontaneous action paintings of Pollock, but in fractal works of art perhaps more than anywhere else. This study, based on Fauconnier and Turner's blended space and conceptual blending theories, will show how fractal artworks are the result of a multi-blending process. This multi-blending is not only because fractal artworks have roots simultaneously in science, technology and art but also because their creation and understanding is dependent on knowledge of fractal aesthetics. Fractal aesthetics not only makes the artist have a continuous back and forth movement between mathematical, digital and artistic spaces, but simultaneously makes the visitor/audience have such an effort as well.1